2001
DOI: 10.1175/1520-0450(2001)040<2038:aannsf>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Neural Network Scheme for Radar Rainfall Estimation from WSR-88D Observations

Abstract: Recent research has shown that neural network techniques can be used successfully for ground rainfall estimation from radar measurements. The neural network is a nonparametric method for representing the relationship between radar measurements and rainfall rate. The relationship is derived directly from a dataset consisting of radar measurements and rain gauge measurements. The effectiveness of the rainfall estimation by using neural networks can be influenced by many factors such as the representativeness and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 4 publications
2
37
0
Order By: Relevance
“…It has been demonstrated in prior work that RBF Neural Network is capable of learning the relation between ground radar measurements and rain gauge data (Liu et al, 2001;Orlandini and Morlini, 2000;Xu and Chandrasekar, 2005;Teschl et al, 2007). In this paper, an adaptive relation between ground radar measurements and rain gauge measurements will be developed in the training process, and studies are conducted to improve the performance of the network.…”
Section: A Alqudah Et Al: Investigating Rainfall Estimation From Ramentioning
confidence: 99%
See 3 more Smart Citations
“…It has been demonstrated in prior work that RBF Neural Network is capable of learning the relation between ground radar measurements and rain gauge data (Liu et al, 2001;Orlandini and Morlini, 2000;Xu and Chandrasekar, 2005;Teschl et al, 2007). In this paper, an adaptive relation between ground radar measurements and rain gauge measurements will be developed in the training process, and studies are conducted to improve the performance of the network.…”
Section: A Alqudah Et Al: Investigating Rainfall Estimation From Ramentioning
confidence: 99%
“…It gets its name from the use of the radial basis function as activation function in the hidden layer. Figure 1 shows the structure of an RBF network (Liu et al, 2001). It contains three layers which are the input layer, the hidden layer and the output layer.…”
Section: Radial Basis Function (Rbf) Neural Network For Rainfall Estimentioning
confidence: 99%
See 2 more Smart Citations
“…Even though the above Z-R equation is rather simple, the relationship between reflectivity and rainfall rate is indeed more complex and has been restricted within Previous work by Liu et al (2001) demonstrated that an adaptive radial basis function neural network was able to provide rainfall estimation fairly accurately. This study was intended for real-time implementation of ANN-based rainfall retrieval algorithm on WSR-88D radars.…”
Section: Radar-based Studiesmentioning
confidence: 99%